The Origin of Water And Its Meaning for Planet Earth (Proceedings of Faculty of Civil Engineering, 2019)
This paper gives a description of the origin of water on planet Earth and its importance in the past and the present. The paper presents the analysis of water flow extent on Earth, its characteristics, as well as the main sources of available water on the planet, expressed through a percentage share on a global scale. It also deals with the origin of water in the Universe, as well as the production of oxygen at the early stages of the planet’s formation. The focus of the paper is based on maintaining the quality of water available on Earth and the global variability of precipitation intensity that has changed the characteristics of large world surfaces through significant drought and flood processes over the last decades. Throughout the paper, some of the most important examples of exploitation of drinking water in the world through the surface and underground reserves of water are described. The possibilities of increasing the production of food for human needs in terms of increasing land through technologically advanced methods and the protection of water resources due to climate change are analyzed. At the end of the paper, there is a review of the characteristics of natural water quality in medicine and industry, sanitary conditions improvement, the impact of global pollution on human beings, economic growth and the problem of water scarcity, as well as the global problem of discharging untreated wastewater into the recipients and consequently endangering flora and fauna.
Keywords: water; water origin; quality and quantity of water; global pollution; climate change; protection methods